Relationship of circulating tumor cells and Epstein–Barr virus DNA to progression‐free survival and overall survival in metastatic nasopharyngeal carcinoma patients. Issue 10 (10th June 2019) - You, Rui; Liu, You‐Ping; Lin, Mei; Huang, Pei‐Yu; Tang, Lin‐Quan; Zhang, Yi‐Nuan; Pan, Yi; Liu, Wan‐Li; Guo, Wei‐Bang; Zou, Xiong; Zhao, Ke‐Ming; Kang, Ting; et al.
Abstract : We analyzed the number of circulating tumor cells (CTCs) and Epstein–Barr virus DNA (EBV DNA) for diagnosis, monitoring and prognosis of patients with metastatic nasopharyngeal carcinoma (mNPC). The levels of CTCs and EBV DNA were measured at baseline and after first‐line chemotherapy in 148 mNPC patients prospectively enrolled between December 2014 and August 2016. We also collected 122 non‐mNPC cases within the same time frame for examining CTCs and EBV DNA at baseline. In 270 NPC patients, we observed improved specificity (86.0% vs . 41.0%) and inferior sensitivity (42.3% vs . 81.3%) of CTCs as compared to EBV DNA for diagnosis of distant metastasis. mNPC patients were stratified into unfavorable and favorable prognostic groups, respectively, based on CTC of 12 at baseline and 1 after first‐line chemotherapy and EBV DNA of 10, 000 at baseline and 4, 000 after first‐line chemotherapy. Conversion of baseline unfavorable CTCs and EBV DNA to favorable after first‐line chemotherapy was associated with significantly longer progression‐free survival (PFS) and overall survival (OS) compared to patients with unfavorable CTCs and EBV DNA at both time points. Among patients with a complete/partial response as per imaging evaluation, favorable CTCs and EBV DNA levels after first‐line chemotherapy were associated with significantly longer PFS and OS. In conclusion, our data demonstrated the number of CTCs and EBV DNA before, after and during first‐line chemotherapy were strong predictive markers for mNPC patients. When utilized in conjunction with imaging studies, CTCs and EBV DNA could provide additional prognostic information. Abstract : What's new? Endemic nasopharyngeal carcinoma (NPC) is associated with latent infection of the oncogenic Epstein‐Barr virus (EBV) and frequently metastasizes to distant lymph nodes and organs. Metastatic NPC is treated by serial administration of cytotoxic or targeted therapies and treatment response is generally assessed with serial imaging, which often fails to detect changes in tumor burden. Here, the authors show that the number of circulating tumor cells (CTCs) and EBV DNA levels before, after, and during first‐line chemotherapy are strong predictive markers for mNPC patients. When utilized in conjunction with imaging studies, CTCs and EBV DNA could provide additional prognostic information.